Rural Enterprise Management Practices: Comparison of Successful and Unsuccessful Rural Entrepreneurs in the Villages of NCR of Delhi - Singh, Rahul; Burman, R. Roy; Sharma, Shailendra; Rao, D.U.M.; Singh, Mukesh (Indian Journal of Extension Education, 2017)
In a study conducted in the villages of NCR of Delhi on rural enterprise management functions being practiced by rural entrepreneurs, it was revealed that majority of successful entrepreneurs were found to practice good management functions such as operational planning, decision-making, delegation, controlling, organizing resources for production, coordination, book-keeping and writing a balance sheet for efficiently running their rural enterprises. A comparison was also attempted to differentiate the successful entrepreneurs with unsuccessful entrepreneurs, Where the differences were found to be statistically significant at least on major enterprise management functions. The study further revealed that successful entrepreneurs were practices primary management functions and financial management functions very well and better than the unsuccessful entrepreneurs. It can be concluded that rural entrepreneurs in general were found to be at par in organizing the resources and coordinating their enterprise management aspects but lack in financial management skills.
Keywords: Rural Enterprise; Enterprise Management Functions; Successful Entrepreneurs; Unsuccessful Entrepreneurs